Trimester-specific associations of maternal exposure to disinfection by-products, oxidative stress, and neonatal neurobehavioral development. (December 2021) - Liu, Chong; Messerlian, Carmen; Chen, Ying-Jun; Mustieles, Vicente; Huang, Li-Li; Sun, Yang; Deng, Yan-Ling; Cheng, Ying-Hui; Liu, Jing; Liu, A-Mei; Lu, Wen-Qing; Wang, Yi-Xin
Highlights: Blood BDCM in the 1st trimester was inversely associated with NBNA scores. Urinary TCAA in the 3rd trimester was inversely related with NBNA scores. These associations were stronger in male infants and mothers aged ≥25 years. We found no evidence of mediating effect by oxidative stress biomarkers. Abstract: Background: Toxicological studies suggest that maternal exposure to disinfection by-products (DBPs) can impair fetal neurodevelopment. However, evidence from epidemiological studies is scarce and the underlying mechanisms remain unclear. Objective: To explore the trimester-specific associations between maternal blood trihalomethane (THM) and urinary haloacetic acid (HAA) concentrations and neonatal neurobehavioral development, and the potential mediating role of oxidative stress (OS). Methods: We included 438 pregnant Chinese women from the Xiaogan Disinfection By-Products (XGDBP) birth cohort. Biospecimens were repeatedly collected across trimesters and measured for blood THMs, urinary HAAs, and urinary OS biomarker concentrations. On the third day after birth, the Neonatal Behavioral Neurological Assessment (NBNA) test was administered to newborns. Associations of trimester-specific DBP measurements and OS biomarkers with neonatal NBNA scores were assessed using linear regression models with generalized estimating equations. The potential mediating role of maternal OS biomarkers was also investigated using mediation analyses. Results: After adjusting for potential confounders, blood bromodichloromethane (BDCM) concentrations in the first trimester were inversely associated with NBNA scores [percent change comparing the extreme BDCM tertiles = –28.1% (95% CI: –55.2%, –0.88%); p for trend = 0.043]. Besides, third-trimester urinary trichloroacetic acid (TCAA) concentrations were inversely associated with NBNA scores [percent change comparing the extreme TCAA tertiles = –32.9% (95% CI: –64.7%, –1.0%); p for trend = 0.046]. These inverse associations differed across pregnancy trimesters (Type 3  p -value = 0.066 and 0.053, respectively) and were stronger in male infants and mothers aged ≥25 years. There was no evidence of mediating effect by 8-hydroxy-2-deoxyguanosine (8-OHdG), 4-hydroxy-2-nonenal-mercapturic acid (HNE-MA), or 8- iso -prostaglandin F2α (8-isoPGF2α ). Conclusions: Higher prenatal BDCM and TCAA concentrations during specific pregnancy trimesters were associated with lower NBNA scores. However, additional research is required to investigate underlying mechanisms.